The THE INFLUENCE OF PERCEPTION OF OIL PALM FARMING PROFESSION AND INCOME ON THE INTEREST OF GENERATION Z IN BECOMING FARMERS IN TANJUNG JATI VILLAGE, BINJAI DISTRICT, LANGKAT REGENCY: The Influence of Perception of the Oil Palm Farming Profession and Income on the Interest of Generation Z in Becoming Farmers in Tanjung Jati Village, Binjai District, Langkat Regency - Cintia Dwi Anindita; Febriana Roosmawati (RADJA PUBLIKA, 2026)
The farmer regeneration crisis is a serious issue for the sustainability of Indonesia's agricultural sector. Data from the 2023 Agricultural Census by the Central Statistics Agency (BPS) shows that Generation Z only accounts for 2.14% of the nation's total farmers, significantly lagging behind Generation X (42.39%) and Baby Boomers (27.61%). This study aims to analyze partially and simultaneously the influence of perceptions of the farmer's profession and oil palm farming income on Generation Z's interest in becoming farmers in Tanjung Jati Village. This study uses a quantitative method with multiple linear regression analysis. The research sample consisted of 93 Generation Z individuals aged 17-29 years who reside in Tanjung Jati Village. Data were collected through a questionnaire with a Likert scale of 1-5. The results of the study indicate that the perception of the farmer profession has a positive and significant effect on Generation Z's interest in becoming a farmer with a t value = 3.286 and Sig. = 0.001, then the income from oil palm farming has a positive and significant effect on Generation Z's interest in becoming a farmer with a t value = 2.605 and Sig. = 0.011. Then the perception of the profession and income from oil palm farming simultaneously have a significant effect on Generation Z's interest in becoming a farmer with a value of F = 28.745 and Sig. = 0.000. The R² value of 0.390 indicates that the two variables explain 39.0% of the variation in Generation Z's interest while the remaining 61.0% is influenced by other factors outside the study.